Acute toxicity of the intranasal administration of Anredera cordifolia extract in Wistar Rats - Asti Widuri; Rifki Febriansah (Universitas Ahmad Dahlan, 2024)
Anredera cordifolia (AC) known as the binahong plant in Indonesia has been commonly used for traditional medicine since the ancients. AC contains secondary metabolites such as flavonoids that have anti-oxidative, anti-inflammatory, anti-mutagenic, and anti-carcinogenic properties. Many flavonoids compound that has anti-inflammatory activity have the potential for the treatment of nasal inflammatory such as allergic rhinitis. This study aims to evaluate the preclinical safety of acute intranasal administration of AC extract in Wistar rats with mortality, clinical changes, blood laboratory, and body weight evaluation. Acute toxicity using the intranasal irrigation administration of AC extract was evaluated on 30 female Wistar rats, divided into five rats for control, and each five of doses 5%, 10%, 25%, 50%, and 75%. We perform blood laboratory after administration and observation for 14 days for the incidence of mortality and signs of toxicity such as tremors, hypoactivity, irregular respiration, and bodyweight loss. The AC extract intranasal administration doses at 5, 10, 25, 50, and 75 did not show mortality, or treatment-related adverse events and did not show significantly changes in blood profile. Based on the study the AC extract was found safe until 75% for nasal administration in Wistar rats.